The management of type 2 diabetes before, during and after Covid-19 infection: what is the evidence - Czupryniak, Leszek; Dicker, Dror; Lehmann, Roger; Prázný, Martin; Schernthaner, Guntram (Cardiovascular diabetology, 2021)
Patients with Covid-19 place new challenges on the management of type 2 diabetes, including the questions of whether glucose-lowering therapy should be adjusted during infection and how to manage a return to normal care after resolution of Covid-19 symptoms. Due to the sudden onset of the pandemic, physicians have by necessity made such important clinical decisions in the absence of robust evidence or consistent guidelines. The risk to patients is compounded by the prevalence of cardiovascular disease in this population, which alongside diabetes is a major risk factor for severe disease and mortality in Covid-19. We convened as experts from the Central and Eastern European region to consider what advice we can provide in the setting of type 2 diabetes and Covid-19, considering the evidence before, during and after infection. We review recommendations that have been published to date, and consider the best available-but currently limited-evidence from large observational studies and the DARE-19 randomized control trial. Notably, we find a lack of guidance on restarting patients on optimal antidiabetic therapy after recovering from Covid-19, and suggest that this may provide an opportunity to optimize treatment and counter clinical inertia that predates the pandemic. Furthermore, we emphasize that optimization applies not only to glycaemic control, but other factors such as cardiorenal protection. While we look forward to the emergence of new evidence that we hope will address these gaps, in the interim we provide a perspective, based on our collective clinical experience, on how best to manage glucose-lowering therapy as patients with Covid-19 recover from their disease and return to normal care.
Keywords: diabetes mellitus 2. typu; rizikové faktory; časové faktory; Insulin; Glycemic Control; Hypoglycemic Agents; Time Factors; hypoglykemika; Diabetes Mellitus, Type 2; lidé; regulace glykemie; inzulin; Practice Guidelines as Topic; Risk Factors; Humans; směrnice pro lékařskou praxi jako téma; COVID-19